Penggunaan Podcast Sebagai Media Alternatif Dalam Pembelajaran Pendidikan Agama Islam Di Era Revolusi Industri 4.0 Di Madrasah Tsanawiyah Daarul Ihya Kecamataan Ciseeng Kabupaten Bogor - Rahmat, Arip; Mufidah, Vika Nurul (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to analyze the use of podcasts as an alternative medium in Islamic Education (PAI) learning and its impact on students’ understanding and learning outcomes at MTs Daarul Ihya Ciseeng. The research employed Classroom Action Research (CAR) with students of grades VII and VIII in the 2024/2025 academic year, totaling 21 students. Data were collected through observation, tests, interviews, and documentation. The CAR procedure consisted of action planning, implementation, observation and interpretation, as well as analysis and reflection carried out in two cycles. The findings show that the use of podcast media in PAI learning can increase students’ interest and learning outcomes. This is indicated by a significant increase in test scores. In cycle I, 14 students (66%) achieved the minimum mastery criterion (KKM) of 65, with an average score of 69.6. In cycle II, 18 students (85%) reached the KKM, with an average score of 75.7, indicating an increase of 6.1 points from cycle I. Thus, podcasts are effective as an alternative medium to improve students’ understanding and learning outcomes in PAI learning at MTs Daarul Ihya Ciseeng.